Survei Pembinaan Prestasi Atlet Renang di Pemalang Shark Swimming Club Tahun 2021 - Muslimin Satrio Anjasmoro; Tommy Soenyoto (Universitas Negeri Semarang, 2023)
The results of this study indicate that the swimming athlete coaching program includes theoretical and practical aspects with reference to the program that has been prepared by the coach, namely the long-term program. The use of this longterm training program can make it easier for coaches to control athlete development. The coaching program that the coach provides also includes the mental aspect, namely by providing reaction and mindset exercises so that athletes do not feel afraid when participating in competitions. Then from the skill aspect, the trainer provides swimming exercises on land and anaerobic on land. And from the physical aspect, the trainer provides additional training, namely running and fitness to maintain athlete fitness. Management at the club still has many shortcomings, especially in the area of funding. Most of the income is obtained only from donations from athletes so that it is only sufficient for internal needs. The infrastructure of the coaching program still uses swimming pools in privately owned tourist attractions, so the coaching takes visitors away from 14.00-17.00. From the results of the study, it is known that the achievements at Pemalang Shark Swimming Club are always consistent in winning in every championship they participate in.